Doctrines for occupational health and safety - Bjurström, Erik (Frontiers in Sustainability, 2022)
The balance between structure and handling of uncertainty through mindfulness remains a riddle in occupational health and safety. In similar vein, the relation between strategy, business models, management control and its influence on actual practice is still poorly understood. Hence, the notion of doctrines is here suggested as a new way of talking about these tensions, as middle-way between abstract models and routines at the one hand, and actual mindful practices on the other. What becomes clear in this exploration is that the tension between structural abstractions on the one side and the concrete everyday – and possibly mindful – practice on the other, are not only theoretical and practical concerns, but touches at the fundamental intelligibility of human action.